The Effect of Plyometric Training on Leg Muscle Explosive Power in Adolescent Amateur Volleyball Players - Muhlasin, Dany Fajar; Nugroho, Fendy; Pertiwi, Jasmine Kartiko (Jurnal Fisioterapi Terapan Indonesia, 2026)
Background: Leg muscle explosive power is a crucial physical component in volleyball, particularly in supporting the execution of smashes and blocks. The ability to generate force rapidly and explosively plays a key role in determining an athlete’s jumping performance. One training method proven effective in enhancing leg muscle explosive power is plyometric exercise. Several recent studies have shown that plyometric training can significantly improve vertical jump performance in adolescent athletes. However, there is still limited research specifically examining the effect of plyometric exercise on jumping explosive power in amateur players aged 14–18 years, indicating a research gap that warrants further investigation. Objective: This study aimed to determine the effect of plyometric training on improving leg muscle explosive power in amateur volleyball players. Methods: This study employed a quasi-experimental design with a pre-test and post-test control group design. The subjects were 32 amateur volleyball players from the Dusun Tegalrejo volleyball team, divided into an intervention group (n = 16) and a control group (n = 16). Leg muscle explosive power was measured using the Vertical Jump Test (VJ). Results: Statistical analysis showed that the intervention group had a significant improvement (p = 0.001, p < 0.05). The comparison between the two groups also revealed a significant difference (p = 0.003, p < 0.05). The intervention group showed a greater mean difference (4.94) compared to the control group (2.43). Conclusion: Plyometric exercise is effective in improving jumping explosive power in amateur volleyball players.